Budget impact of somatostatin analogs as treatment for metastatic gastroenteropancreatic neuroendocrine tumors in US hospitals - Ortendahl JD; Pulgar SJ; Mirakhur B; Cox D; Bentley TGK; Phan AT (Dove Medical Press, 2017)
Jesse D Ortendahl,1 Sonia J Pulgar,2 Beloo Mirakhur,3 David Cox,3 Tanya GK Bentley,1 Alexandria T Phan4 1Health Economics, Partnership for Health, LLC, Beverly Hills, CA, USA; 2Health Economics and Outcomes Research, Ipsen Biopharmaceuticals, Basking Ridge, NJ, USA; 3Medical Affairs, Oncology, Ipsen Biopharmaceuticals, Basking Ridge, NJ, USA; 4GI Medical Oncology, University of New Mexico Comprehensive Cancer Center, Albuquerque, NM, USA Objective: With the introduction of new therapies, hospitals have to plan spending limited resources in a cost-effective manner. To assist in identifying the optimal treatment for patients with locally advanced or metastatic gastroenteropancreatic neuroendocrine tumors, budget impact modeling was used to estimate the financial implications of adoption and diffusion of somatostatin analogs (SSAs). Patients and methods: A hypothetical cohort of 500 gastroenteropancreatic neuroendocrine tumor patients was assessed in an economic model, with the proportion with metastatic disease treated with an SSA estimated using published data. Drug acquisition, preparation, and administration costs were based on national pricing databases and published literature. Octreotide dosing was based on published estimates of real-world data, whereas for lanreotide, real-world dosing was unavailable and we therefore used the highest indicated dosing. Alternative scenarios reflecting the proportion of patients receiving lanreotide or octreotide were considered to estimate the incremental budget impact to the hospital. Results: In the base case, 313 of the initial 500 gastroenteropancreatic neuroendocrine tumor patients were treated with an SSA. The model-predicted per-patient cost was US$83,473 for lanreotide and US$89,673 for octreotide. With a hypothetical increase in lanreotide utilization from 5% to 30% of this population, the annual model-projected hospital costs decreased by US$488,615. When varying the inputs in one-way sensitivity analyses, the results were most sensitive to changes in dosing assumptions. Conclusion: Results suggest that factors beyond drug acquisition cost can influence the budget impact to a hospital. When considering preparation and administration time, and real-world dosing, use of lanreotide has the potential to reduce health care expenditures associated with metastatic gastroenteropancreatic neuroendocrine tumor treatments. Keywords: health economics, oncology, model, costs, real-world evidence, lanreotide